2009
DOI: 10.1007/s00330-008-1260-y
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic 3D fast spin-echo imaging versus standard 2D imaging at 3.0 T of the knee—image quality and diagnostic performance

Abstract: Isotropic 3D fast spin-echo imaging versus standard 2D imaging at 3.0 T of the knee-image quality and diagnostic performance Abstract The objective of this study was to compare a newly developed fat-saturated intermediate-weighted (IM-w) 3D fast spin-echo (FSE) sequence with standard 2D IM-w FSE sequences regarding image quality and diagnostic performance in assessing abnormal findings of the knee. MR imaging was performed at 3.0 T in 50 patients. Images were assessed independently by three radiologists. Image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 24 publications
2
73
0
Order By: Relevance
“…23 Although 3D reformatted images have indistinct margins, and therefore decreased spatial resolution, this problem did not occur in our evaluation of PCL injury. 24 We can attribute these results to the fact that the diagnosis of PCL injury is based on whether or not the PCL has its own continuity and whether or not there is homogeneous low signal intensity of the ligament, which explains why inferior sharpness does not affect diagnostic performance. Thus, we suggest that 3D VISTA can replace 2D FSE in the evaluation of PCL injury without sacrificing diagnostic ability.…”
Section: Resultsmentioning
confidence: 96%
“…23 Although 3D reformatted images have indistinct margins, and therefore decreased spatial resolution, this problem did not occur in our evaluation of PCL injury. 24 We can attribute these results to the fact that the diagnosis of PCL injury is based on whether or not the PCL has its own continuity and whether or not there is homogeneous low signal intensity of the ligament, which explains why inferior sharpness does not affect diagnostic performance. Thus, we suggest that 3D VISTA can replace 2D FSE in the evaluation of PCL injury without sacrificing diagnostic ability.…”
Section: Resultsmentioning
confidence: 96%
“…This finding is in keeping with the preliminary results from previous studies undertaken using 3-T systems, which demonstrated lower or similar diagnostic performance in comparison with conventional two-dimensional (2D) imaging. [2][3][4] However, other 3-T studies have shown promising results for the evaluation of menisci by a 3D sequence with no statistical difference in the evaluation of surgically confirmed meniscal tears. 5,6 A larger study by Kijowski and associates demonstrated that a 3D SPACE sequence had a similar sensitivity and specificity for evaluating medial meniscal tears compared with a routine MRI protocol and a similar specificity in evaluating the lateral meniscus but a significantly reduced sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Up until now, the majority of studies assessing 3D SE sequences in the knee have been undertaken on 3-T MRI systems. [2][3][4][5][6][7][8][9][10][11] However, in common with many centres, our institution employs a 1.5-T system for the majority of its routine knee MRI studies. With acquisition time being a key factor in knee imaging protocols, our aim was to assess whether reconstructions obtained from a single isotropic 3D FSE PD (FS) sequence could replace the 3 PD (FS) sequences in our standard protocol on a 1.5-T system (Siemens Avanto, Erlangen, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…However, recently it was observed increased use of two-dimensional intermediate-weighted sequence. This sequence was suitable to evaluate all knee joints, due to suitable appropriate tissue contrast and high spatial resolution (Jung et al 2009, Ristow et al 2009, Kijowski 2010, Van Dyck et al 2012. Further study on this sequence to assess the stifle joint in the dog should be performed.…”
Section: Resultsmentioning
confidence: 99%